Medsebojna povezanost inteligentnosti, glasbenih aktivnosti in družinskega okolja pri devetošolcih - Kopačin, Barbara (Revija za elementarno izobraževanje, 2014)
The Interrelation of Intelligence, Involvement in Musical Activities, and Supportive Musical Family Environment in Ninth-Graders. Intelligence has increasingly been becoming a desirable human trait, so she scientists from different fields devote it a lot of attention. We were interested in the interconnectedness of intelligence, musical activities and family environment in ninth graders. Correlations were determined with the differences in student achievement in measuring educative components of general intellectual abilities with standard progressive matrices (SPM). The survey results confirm that intelligence, musical activities and musical family environment significantly correlated with each other. The study included 177 randomly selected ninth graders from six basic schools in the region of Primorska.
Keywords: Raven’s progressive matrices; intelligence; musical family environment; formal music education; music activities